Pengaruh Kualitas Produk, Citra Merek, Kepercayaan Konsumen Terhadap Keputusan Pembelian Motor Yamaha Mio - Ina Sulistianti; Sulistiono Sulistiono (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine whether the effect of Product Quality, Brand Image, and Consumer Trust partially and simultaneously influence the Purchase Decision. The population in this study are consumers who use or have used Yamaha Mio in Bogor City with a total sample of 170 people. Data testing is done using SPSS 23 software. The results of this study are as follows: (1) Product quality partially influences purchasing decisions with a t count value greater than t table (2,996 > 1.65). (2) Brand Image partially influences purchasing decisions with the t-count value greater than t-table (2.892 < 1.65). (3) Consumer Confidence partially influences purchasing decisions with a t-count value greater than t-table (3.903 > 1.65). (4) Product Quality, Brand Image, and Consumer Trust simultaneously have a positive and significant effect on Purchase Decisions with a calculated F value greater than F table (45.189 > 2.66) and a significance value of 0.000. Keywords : Effect of Product Quality, Brand Image, Consumer Trust and Purchase Decision.